Efficacy and tolerability of colonoscopies in overweight and obese patients: Results from a national database on gastrointestinal endoscopic outcomes - Passi, Monica; Rahman, Farial; Koh, Christopher; Kumar, Sheila (Endoscopy International Open, 2022)
Background and study aims Gastroenterologists are encountering a rising number of obese patients requiring colonoscopy. Existing literature regarding colonoscopy outcomes in this population is scant and conflicting. We analyzed a nationwide cohort of patients to identify the effects of body mass index (BMI) on colonoscopy success, efficacy, and tolerability.Patients and methods The Clinical Outcomes Research Initiative (CORI) endoscopic database was queried for all colonoscopies in adults between 2008–2014. Patients were stratified into four cohorts based on BMI classification for comparison. Multivariable analysis was performed to identify the effect of BMI on procedure outcome, efficacy and tolerability.Results Of 41,401 procedures, 27,696 met study inclusion criteria. Of these, 49.4 % were performed for colorectal cancer screening, most commonly under anesthesia directed sedation. Patient discomfort was the reason for an incomplete colonoscopy in 18.7 % of all cases, and more frequent among the overweight and obese cohorts. An inadequate bowel preparation was most common in the class III obesity cohort. Compared to the normal BMI group, a BMI ≥ 30 and < 40 kg/m2 was associated with an increased odds of an incomplete colonoscopy (P = 0.001for overweight, P = 0.0004 for class I/II obesity), longer procedure (P < 0.05 for all) and poorer tolerance (P < 0.0001 for class I/II obesity, P = 0.016 for class III obesity). Anesthesia-administered sedation was more commonly used than endoscopist directed sedation amongst the obese cohort compared with the normal BMI cohort (P < 0.0001).Conclusions Endoscopists should consider the increased odds of incomplete colonoscopy, longer procedures, and poorer tolerance when performing colonoscopy in obese patients to improve clinical management and procedural outcome.